Implementation Of Scout Extraculiculars In The Framework Of Forming Pancasila Student Profiles Of MI Ar-Raudhah Students - joy irvansyah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Basically, education aims to be able to develop abilities and form the character and civilization of a dignified nation in order to educate the nation's life, and achieve the development of the potential of students to become human beings who are faithful and devoted to God Almighty, healthy, knowledgeable, noble, capable, independent, creative, and become democratic and responsible citizens. This type of research is field research using qualitative methods. The research was conducted at MI Ar-Raudhah Hampalit Village, Kahayan Hilir District, Katingan Regency. This research focuses on students in grades IV, V, and VI in the 2023/2024 school year, and this research was conducted for one month in August 2023. Sampling was carried out during the implementation of the activity, with a sample of student representatives and coaches, and the school principal. Data collected in the form of interviews. Extracurricular Scouting in its implementation is related to the framework of embedding the Pancasila student profile in students, because the six important points emphasized in the Pancasila Student Profile are contained in the implementation of extracurricular Scouting, namely related to the Dasa Dharma Scout. At MI Ar- Raudhah school itself, the implementation of Scout Extracurricular is able to assist in assisting in the cultivation of various aspects of the Pancasila student profile